The Importance of Temperature and Potential Window in Stability Evaluation of Supported Pt-Based Oxygen Reduction Reaction Electrocatalysts in Thin Film Rotating Disc Electrode Setup. Issue 11 (17th July 2020) - Maselj, Nik; Gatalo, Matija; Ruiz-Zepeda, Francisco; Kregar, Ambrož; Jovanovič, Primož; Hodnik, Nejc; Gaberšček, Miran
Abstract : The present study showcases the importance of temperature and potential window for evaluation of Pt-based supported electrocatalyst stability. A platinum based commercial material with an average size of Pt nanoparticles between 2–3 nm (Pt/C) and its thermally annealed analogue with an average particle size of ∼5 nm (Pt/C-HT) are considered. X-ray diffraction (XRD), ex situ transmission electron microscopy (TEM) imaging and thin film rotating disc electrode (TF-RDE) along with proprietary high-temperature disc electrode (HT-DE) are used for electrocatalysts inspection. The study shows a clear dependence between the electrochemical surface area (ECSA) loss and the temperature increase during the potentiodynamic accelerated degradation test (ADT). Additionally it is demonstrated that selection of the lower and upper potential limits in ADT protocol plays an important role in ECSA loss. Comparing various results obtained on Pt/C and Pt/C-HT, we show that varying ADT conditions of temperature and different potential windows is crucial for adequate evaluation and stability interpretation of potentially promising novel electrocatalysts and that relatively mild ADT conditions (i.e. 0.4–1.0 VRHE, RT) can be potentially misleading.